Sean Griswold's head - Leavitt, Lindsey (New York : Scholastic, 2011)
After discovering that her father has multiple sclerosis, fifteen-year-old Payton begins counselling sessions at school, which lead her to become interested in a boy in her biology class, have a falling out with her best friend, develop an interest in bike riding, and eventually allow her to come to terms with life's uncertainties.
M
640
M
Keywords: Emotional problems -- Juvenile fiction; Multiple sclerosis -- Juvenile fiction; Families -- Pennsylvania -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Emotional problems -- Fiction; Multiple sclerosis -- Fiction; Family life -- Pennsylvania -- Fiction; High schools -- Fiction; Schools -- Fiction